2019
DOI: 10.3390/molecules24040775
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Diabetic Microenvironment Augments the Decay Rate of Capsaicin-Induced Currents in Mouse Dorsal Root Ganglion Neurons

Abstract: Individuals with end-stage diabetic peripheral neuropathy present with decreased pain sensation. Transient receptor potential vanilloid type 1 (TRPV1) is implicated in pain signaling and resides on sensory dorsal root ganglion (DRG) neurons. We investigated the expression and functional activity of TRPV1 in DRG neurons of the Ins2+/Akita mouse at 9 months of diabetes using immunohistochemistry, live single cell calcium imaging, and whole-cell patch-clamp electrophysiology. 2′,7′-Dichlorodihydrofluorescein diac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In LPA-induced mouse models ( Ohsawa et al, 2013 ) and STZ-induced diabetic mouse models ( Hong et al, 2008 ), TRPV1 was also expressed in large cells of the DRG. The DRG in Akita mice, an animal model of type 1 DM ( Chen et al, 2019 ), also showed increased TRPV1-positive cells. This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In LPA-induced mouse models ( Ohsawa et al, 2013 ) and STZ-induced diabetic mouse models ( Hong et al, 2008 ), TRPV1 was also expressed in large cells of the DRG. The DRG in Akita mice, an animal model of type 1 DM ( Chen et al, 2019 ), also showed increased TRPV1-positive cells. This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of reactive oxygen species (ROS) level. cellular roS level was measured fluorometrically using the ROS sensitive dye 2'-7'-dichlorodihydrofluorescein diacetate (DCFH-DA) as described by chen et al (33). Briefly, H19-7/IGF-IR cells treated as indicated were collected, centrifuged at 500 x g for 5 min at room temperature, resuspended in PBS with dcFH-da (10 µM), and incubated at room temperature for 30 min in darkness.…”
Section: Methodsmentioning
confidence: 99%
“…118 In the long-term diabetic microenvironment, earlier studies demonstrated that TRPV1 desensitization in DRGs decreased TRPV1 activity and contributed to peripheral diabetic neuropathy. 146 Furthermore, the injection of capsaicin attenuated hyperglycaemia in Zucker diabetic fatty animals which is a model of human type 2 diabetes mellitus. 145 In this sense, TRPV1 knockout mice exhibited impairment in glucose metabolism manifested by a decrease in glucose-induced insulin secretion.…”
Section: Trpv1 and Diabetesmentioning
confidence: 99%